The role of financial literacy, digital literacy, and the influence of efficacy in improving the performance of MSME actors in Makassar City - Rezki Anggreni; Muchriana Muchran (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to determine the influence of financial literacy, digital literacy, and the influence of MSME community efficacy on MSME performance. This research takes a quantitative approach with the data source used is primary data obtained from MSME business actors. The sample used in this study was 30 respondents to MSME business actors. The results of this study show that partial financial literacy does not have a significant positive effect on the performance of MSMEs. Digital literacy has a significant positive effect on the performance of MSMEs. Meanwhile, the effect of efficacy does not have a significant positive effect on the performance of MSMEs.